2017
DOI: 10.1038/s41522-017-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis biofilm development in the presence of soil clay minerals and iron oxides

Abstract: Clay minerals and metal oxides, as important parts of the soil matrix, play crucial roles in the development of microbial communities. However, the mechanism underlying such a process, particularly on the formation of soil biofilm, remains poorly understood. Here, we investigated the effects of montmorillonite, kaolinite, and goethite on the biofilm formation of the representative soil bacteria Bacillus subtilis. The bacterial biofilm formation in goethite was found to be impaired in the initial 24 h but burst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…SEM images showed that MIL-100 and Fe-BTC were highly aggregated, while MIL-88A was comprised of small, well-defined crystals approximately the same size as MR-1 (Figure S5). Based on its morphology, MIL-88A is unlikely to support biofilm development (22, 23) . Although they are morphologically similar, MIL-100 and Fe-BTC vary significantly in accessible surface area.…”
Section: Resultsmentioning
confidence: 99%
“…SEM images showed that MIL-100 and Fe-BTC were highly aggregated, while MIL-88A was comprised of small, well-defined crystals approximately the same size as MR-1 (Figure S5). Based on its morphology, MIL-88A is unlikely to support biofilm development (22, 23) . Although they are morphologically similar, MIL-100 and Fe-BTC vary significantly in accessible surface area.…”
Section: Resultsmentioning
confidence: 99%
“…In many cases, a buffered defined medium using glutamic acid, as the sole nitrogen source, and glycerol, as the sole carbon source, is used to trigger production of the biofilm matrix (Branda et al, ). A few studies have also examined biofilm formation of model strains in different growth conditions (Dogsa et al, ; Ma et al, ), while limited insights into the diversity of biofilm regulation and biofilm properties of different B. subtilis isolates have been acquired (Oslizlo et al, ; Sanchez‐Vizuete et al, ; Yu et al, ).…”
Section: Division Of Labour In Biofilm Formationmentioning
confidence: 99%
“…However, microorganisms in the natural environment frequently exist as surface-attached structures termed biofilms (Flemming and Wingender, 2010;McDougald et al, 2011;Flemming et al, 2016). Biofilms generally colonize carbon rich surfaces of soil media such as plant roots and clay minerals, and secrete EPS to form aggregates (Ma et al, 2017;Nunan, 2017;Cai et al, 2018). The multicellular aggregates formed by soil microbes are known as soil biofilms, or unsaturated biofilms, owing to low water availability as the distinguishing environmental factor of the local environment (Holden, 2001).…”
Section: The Soil Microbiome and Biofilmsmentioning
confidence: 99%